Higher Degree of Left Atrial Structural Remodeling in Patients with Atrial Fibrillation and Left Ventricular Systolic Dysfunction. - Akkaya, Mehmet; Higuchi, Koji; Koopmann, Matthias; Damal, Kavitha; Burgon, Nathan S.; Kholmovski, Eugene; McGANN, Chris; Marrouche, Nassir (Journal of Cardiovascular Electrophysiology, 2013)
LV Systolic Dysfunction is Related to LA-SRM in AF Patients Background Catheter ablation significantly improves the left ventricular (LV) function in patients with atrial fibrillation (AF) and LV systolic dysfunction. In this study, we compared the degree of left atrial structural remodeling (LA-SRM) in patients with normal versus reduced LV ejection fraction (LVEF). We also studied the impact of LA-SRM on LVEF improvement in patients undergoing ablation of AF. Method and Results We categorized 384 patients into 2 groups based on their cardiac function: reduced LVEF group (LVEF ≤50%; n = 105) and normal LVEF group (LVEF > 50%; n = 279). LVEF was determined prior and mean 8 ± 3 months after catheter ablation for AF. Percentage of LA-SRM was quantified using LGE-MRI and patients were classified into 4 groups based on the amount of structural remodeling in their LA wall: minimal ≤ 5%, mild = 5-20%, moderate = 20-35%, and extensive ≥ 35%. The average preablation LA-SRM (21.5 ± 13.2% vs 15.4 ± 10.0%; P < 0.001) was significantly higher in reduced LVEF group than normal LVEF group. Among the 105 patients with reduced LVEF, while there was a modest 11.7 ± 8.4% average increase in LVEF following ablation, the greatest increase was seen in patients with less extensive LA-SRM (minimal = 19.3 ± 5.1%, n = 3, P = 0.02 and mild = 16.6 ± 9.9%, n = 48, P < 0.001). Patients with moderate and extensive fibrosis had an average EF improvement of 8.7 ± 11.1% and 2.8 ± 6.4%, respectively (n = 39, P < 0.001 and n = 15, P = 0.11, respectively). Conclusion Patients with LV systolic dysfunction displayed a comparatively greater LA-SRM than patients with normal LVEF. Patients with lesser LA-SRM experienced a greater improvement in LVEF after catheter ablation for AF.